Evaluation of the Experiences of Turkish Orthopedists Caught in Covid-19 - Tanrıverdi, Bülent; Hürmeydan, Önder Murat; Bilgili, Mustafa Gökhan (Cerrahpaşa Medical Journal, 2021)
Objective: Coronavirus disease-2019 (Covid-19) emerged in December 2019 in Wuhan, Hubei province, China. Today, Covid-19 threatens the health of the whole world and the whole population. In this study, we aimed to investigate the processes experienced by orthopedists in our country in the Covid-19 pandemic. Methods: A total of 45 orthopedic surgeons, including 15 Covid-19 patients (+) and 30 Covid-19 (−) control groups, were included in the study. All participants were asked to fill out a questionnaire containing both professional and demographic information and information about Covid-19, and these results were evaluated. Results: According to the results of the survey, it was determined that 13 people in the patient group of 15 people showed symptoms. Among the symptoms, myalgia (66.7%), fever (40%), and cough (40%) were in the first 3 places. In the patient group, the cause of transmission was related to the hospital in 9 people. It was found that 6 people from the patient group transmitted the disease to family members. Nine patients in the patient group had no laboratory findings. Hydroxychloroquine was used alone in 6 patients as medical treatment, while 3 or 4 drug combinations were used in the remaining 9 patients. Ten patients were treated as outpatients, 5 patients were hospitalized. Conclusion: It can be said that this infectious disease, which has affected the whole world from the day it began, has a similar course in our country and has similar characteristics with the world literature in terms of orthopedic surgeons. Continuing health services without interruption and preventing occupational exposure will be possible with adequate training, use of protective equipment, and compliance with hygiene rules. Cite this article as: Tanrıverdi B, Hürmeydan ÖM, Bilgili MG. Evaluation of the experiences of Turkish orthopedists caught in Covid-19. Cerrahpaşa Med J. 2021;45(3):210-215.